1991
DOI: 10.1002/lsm.1900110612
|View full text |Cite
|
Sign up to set email alerts
|

Studies in fiber guided excimer laser surgery for cutting and drilling bone and meniscus

Abstract: Our experiments on transmitting high-power excimer laser pulses through optical fibers and our investigations on excimer laser ablation of hard tissue show the feasibility of using the excimer laser as an additional instrument in general and accident surgery involving minimal invasive surgery. By combining XeClexcimer lasers and tapered fused silica fibers we obtained output fluences up to 32 J/cm2 and ablation rates of 3 pdpulse of hard tissue. This enables us to cut bone and cartilage in a period of time whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Studies of cortical bone healing following laser osteotomy have been reported for the 193 nm [4,5], 248 nm [2,5] and 308 nm [1,3] [6, 12±16] lasers. The in¯uence on bone healing of various continuous wave and pulse modes, using various irradiances and¯uences of these laser wavelengths, have been examined and compared to drill or osteotomy saw lesions, in a variety of rat and rabbit in vivo models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of cortical bone healing following laser osteotomy have been reported for the 193 nm [4,5], 248 nm [2,5] and 308 nm [1,3] [6, 12±16] lasers. The in¯uence on bone healing of various continuous wave and pulse modes, using various irradiances and¯uences of these laser wavelengths, have been examined and compared to drill or osteotomy saw lesions, in a variety of rat and rabbit in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…One study, using a ®ber guided 308 nm excimer laser to ablate cortical bone under a water surface, reported no carbonization of the ablation site and a preliminary healing study that found no difference in healing of osteotomy holes drilled in rabbit tibia cortex with either the laser or mechanical instruments [3]. A recent report indicated good healing following 193 and 248 nm irradiation; however, no comparison was made to a mechanical cut control group, and no discussion was presented comparing these results to previous studies with these wavelengths where healing has been delayed [5].…”
Section: Discussionmentioning
confidence: 99%
“…The laser beam can be tightly focused and its position controlled electronically, so that precise narrow cuts with arbitrary complicated geometry can be exactly planned and performed. Early attempts to cut bones with lasers have failed however, because of strong thermal side effects in case of continuous wave (cw) and long-pulsed carbon dioxide CO 2 lasers 1-5 or very low cutting rate with excimer lasers [6][7][8][9] . The difficulties arise, while about one third of the compact bone tissue volume consists of hard mineral crystals (T melt > 1000°C 10,11 ), which are embedded in a sensitive collagen matrix.…”
Section: Introductionmentioning
confidence: 99%
“…When MMF are used for high-power excimer laser light delivery [8,9], the surface damage threshold of synthetic silica is the primary limit. Severe optical damage is observed at power densities above 1 GW/cm² for pulsed lasers [10].…”
Section: Introductionmentioning
confidence: 99%